Current knowledge of COVID-19 and infection prevention and control strategies in healthcare settings: A global analysis. (15th October 2020) - Islam, M. Saiful; Rahman, Kazi M.; Sun, Yanni; Qureshi, Mohammed O.; Abdi, Ikram; Chughtai, Abrar A.; Seale, Holly
Abstract: Objective: In the current absence of a vaccine for COVID-19, public health responses aim to break the chain of infection by focusing on the mode of transmission. We reviewed the current evidence on the transmission dynamics and on pathogenic and clinical features of COVID-19 to critically identify any gaps in the current infection prevention and control (IPC) guidelines. Methods: In this study, we reviewed global COVID-19 IPC guidelines by organizations such as the World Health Organization (WHO), the US Centers for Disease Control and Prevention (CDC), and the European Centre for Disease Prevention and Control (ECDC). Guidelines from 2 high-income countries (Australia and United Kingdom) and from 1 middle-income country (China) were also reviewed. We searched publications in English on 'PubMed' and Google Scholar. We extracted information related to COVID-19 transmission dynamics, clinical presentations, and exposures that may facilitate transmission. We then compared these findings with the recommended IPC measures. Results: Nosocomial transmission of SARS-CoV-2 in healthcare settings occurs through droplets, aerosols, and the oral–fecal or fecal–droplet route. However, the IPC guidelines fail to cover all transmission modes, and the recommendations also conflict with each other. Most guidelines recommend surgical masks for healthcare providers during routine care and N95 respirators for aerosol-generating procedures. However, recommendations regarding the type of face mask varied, and the CDC recommends cloth masks when surgical masks are unavailable. Conclusion: IPC strategies should consider all the possible routes of transmission and should target all patient care activities involving risk of person-to-person transmission. This review may assist international health agencies in updating their guidelines.